A CONCEPTUAL OVERVIEW OF CONTEXT TYPES - Ramila Rzayeva (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This article examines the concept of context as a multidimensional and dynamic system in modern linguistics and literary studies. Moving beyond the traditional understanding of context as the immediate verbal environment of a word or expression, the text argues that context includes a wide range of factors such as speaker intention, communicative situation, cultural codes, ideological background, and relations to prior texts. The study identifies four major types of context: situational, cultural, pragmatics, and intertextual. Although discussed separately for analytical purposes, these categories are shown to function in constant interaction within literary discourse. The article draws on theories from linguistics, pragmatics, stylistics, discourse analysis and literary criticism, while also referring to literary works by Kazuo Ishiguro, lan McEwan, Zadie Smith, and Toni Morrison to illustrate how context shapes interpretation and meaning. Special attention is given to the role of context in producing psychological depth, ideological ambiguity, and aesthetic effect. The article concludes that context should not be seen as a passive background to meaning, but as an active mechanism through which meaning is created, reconstructed, and negotiated in discourse. In this sense, context becomes one of the central forces determining the semantic and discursive structure of literary texts.